Intensive short-term dynamic psychotherapy for irritable bowel syndrome: a randomized controlled trial examining improvements in emotion regulation, defense mechanisms, quality of life, and IBS symptoms - Shafiei, Faezeh; Dehghani, Mahmood; Lavasani, Fahimeh Fathali; Manouchehri, Mehdi; Mokhtare, Marjan (Frontiers in Psychology, 2024)
Studies have provided evidence for the effectiveness of intensive short-term dynamic psychotherapy (ISTDP) in treating medically unexplained symptoms (MUS). This study aimed to examine the effectiveness of ISTDP on individuals living with irritable bowel syndrome (IBS) in terms of, emotion regulation (ER) abilities, defense mechanisms, quality of life (QOL), and IBS symptoms. A total of 30 patients diagnosed with IBS were recruited and randomly assigned to either the intervention (n = 15) or control (n = 15) group. Pre-and post-treatment assessments were conducted, along with a follow-up assessment after ten weeks. Repeated measures analyses of variance were employed to analyze the data. The findings revealed that ISTDP led to significant improvements in ER, defense mechanisms, and QOL, as well as a reduction in the severity and frequency of IBS symptoms. These results provide further support for the efficacy of ISTDP as a treatment modality for individuals with IBS.